School-based depression and anxiety prevention programs: An updated systematic review and meta-analysis - Werner-Seidler, Aliza; Spanos, Samantha; Calear, Alison L.; Perry, Yael; Torok, Michelle; O'Dea, Bridianne; Christensen, Helen; Newby, Jill M. (Clinical Psychology Review, 2021)
Depression and anxiety are often first experienced during childhood and adolescence, and interest in the prevention of these disorders is growing. The focus of this review was to assess the effectiveness of psychological prevention programs delivered in schools, and to provide an update to our previous review from five years ago (Werner-Seidler, Perry, Calear, Newby, & Christensen, 2017). Three electronic databases were systematically searched for published articles of randomised controlled trials (RCTs) evaluating the efficacy of school-based prevention programs until October 2020. There were 130 articles that met inclusion criteria, representing 118 unique trials and 45,924 participants. Small between-group effect sizes for depression (g = 0.21) and anxiety (g = 0.18) were detected immediately post-intervention. Subgroup analyses suggested that targeted prevention programs (for young people with risk factors or symptoms) were associated with significantly greater effect sizes relative to universal programs for depression, which was confirmed by meta-regression. There was also some evidence that external providers conferred some benefit over school-staff delivered programs. Overall, study quality was moderate and no association between risk of bias and effect size was detected. School-delivered psychological prevention programs have small effects in reducing symptoms of depression and anxiety. Refinement of these programs, and knowledge about how they can be sustainably delivered in schools beyond the trial period is now needed for population-level preventive effects. Systematic Review Registration Number: PROPSERO - CRD42020188323
Keywords: Anxiety; Depression; Meta-analysis; School-based; Systematic-review